Video Profil Pemandian Sapta Tirta Pablengan Matesih Kabupaten Karanganyar - ., Kusmiyati; Nugroho, Gesang Kristianto (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
Multimedia is one represent of way correct to water down  to submit the information in the form of visual audio or visual. The multimedia also can be result  the something more live and draw, of one applying  multimedia is to visualizing the profile video. The Bath Water Sapta Tirta pablengan not yet owned the medium to promote  to society. By using profile  video expected to earn as a means of promotion  to society at the same time as documentation.The abbreviation  of problem from this research is how to  make the profile The Bath Water Warm of Bayanan by using multimedia computer. As for intention of this  research is to make the  profile video and information media The Bath Water Warm of Bayanan. The benefit from  the research can use is as a promotion media and documentation  of The Bath Water Sapta Tirta pablengan. The reseach methodologies  used by book, observation, the interview, analysis, scheme, in take draw and capturing, editing and voice  recording, test-drive and implementation.Conclusin from making of profile video by using this computer multimedia the purpose of the documentation  of the same  time as promotion medium.